Open Access Monographs: Making Mandates Reality - Eve, Martin Paul; Grady, Tom (Septentrio Conference Series, 2022)
Watch the VIDEO. In early 2022 the major research funding body in the UK (UKRI), released a policy statement mandating Open Access (OA) monographs, with an implementation date of January 1st, 2024. This date will see a shift from a hypothetical future for OA books to a concrete policy with a hard deadline. Add to this the forthcoming mandates on OA books from cOAlition S/Plan S in Europe, and potential implications of the next research impact evaluation (REF) in the UK, and it is clear that there is a pressing need for libraries and academic book publishers to understand how the sector will meet the challenges of implementing these policies. In this session we will present the following questions: what is the transition to open access for scholarly books going to look like? What pitfalls and opportunities will it bring? Who is at risk of being excluded? How do we get from where publishing and libraries are today, to making these policies a workable reality in 2024? We will also pose the crucial question: how will this transition be paid for? We’ll demonstrate how Book Processing Charges (BPCs) worsen inequality by favouring the most wealthy institutions and authors. And we’ll highlight some collective library funding models that seek to spread the funding of OA books so that no single institution bears a disproportionate cost. These models range from the large and well-funded like MIT’s Direct 2 Open and Michigan’s Fund to Mission, to the COPIM project’s own Opening the Future model which is aimed at smaller mission-driven publishers like CEU Press and Liverpool University press. With the clock ticking on imminent policies, conversation is urgently needed on the practicalities of making mandates reality. We’ll discuss what libraries can do to meet the challenge, and how supporting programmes like Opening the Future will ensure that the transition to OA is a sustainable and bibliodiverse one. The transition to OA should not leave smaller and medium-sized presses behind; nor should it rely on paying BPCs, which risks excluding any author without funding; and the transition must be sustainable for libraries. We will demonstrate that the time to support collective funding programme pilots is now, in order that they can transition from pilot to implementable policy, to the benefit of all: opening up research for the public good and building an open, global ‘collection’ that is shared by libraries in common, around the world.